Navigating Challenge, Growth, And Innovation: Stories of Student Entrepreneurs in A Philippine State College (Research and Analysis Journal, 2025)
This study explored the lived experiences of student entrepreneurs at Camarines Sur Polytechnic Colleges (CSPC) through a qualitative narrative inquiry approach. Seven participants, each managing a small business while enrolled in college, were purposively selected and interviewed in August 2025. Their narratives revealed five key themes: (1) entrepreneurship as a survival strategy, (2) time management tug-of-war, (3) resilience through struggles, (4) innovation born from limitations, and (5) learning beyond the classroom. Most participants engaged in entrepreneurship out of financial necessity, using their ventures to sustain education-related and family expenses. Despite academic pressures and limited institutional support, the participants demonstrated adaptability and creativity—often leveraging digital platforms to operate their businesses with minimal resources. The study concludes that student entrepreneurship fosters not only income generation but also the development of critical life skills. However, the dual demands of academics and business create stress and role conflict. Based on the findings, it is recommended that CSPC establish targeted support systems such as mentorship programs, flexible academic arrangements, and integration of entrepreneurial learning into the curriculum. Recognizing and supporting student entrepreneurs can enhance their well-being, academic success, and long-term entrepreneurial potential.